The psychophisiology and the development of clinic psychology - Beteta Pacheco, Edmundo (1999)
Up to date anatomical and biochemistry studies related to Brain mechanisms of behavior are reviewed. This type of research shold be work up in clinical psychology related to prevention, diagnostic and therapy of behavior disorders. In this way, the clinical psychology should make clinical research at differents age groups of the population. He will be able to study epidemiological risk factors together with neuropsychologycal tests and Brain imagind studies.